A Review of Fiqh Muamalah, the Compilation of Sharia Economic Law, and DSN–MUI Fatwas on the Ijarah Muntahiyah Bittamlik Contract at BMT Surya Madani - Waluyo; Falaq Nur Ahmad Hasan; Dewi Permata Sari; Imam Iqbal Nursidiq (Aghnina : Jurnal Hukum Ekonomi Syari'ah, 2026)
The Ijarah Muntahiyah Bittamlik (IMBT) contract is applied as a financing scheme for productive assets at BMT Surya Madani. Its implementation is examined based on the principles of Fiqh Muamalah, the Compilation of Sharia Economic Law (KHES), and Fatwa DSN-MUI No. 27/DSN-MUI/III/2002. Data were collected through field studies using interviews, observation, and documentation, and were analyzed using a normative-comparative approach. The findings indicate that the implementation of IMBT at BMT Surya Madani fulfills the pillars and requirements of the ijarah contract and does not involve elements of riba or gharar. The financing mechanism involves asset acquisition by BMT, leasing to members during the contract period, and the transfer of ownership through a grant at the end of the lease term. Although the ijarah contract and the grant promise are set out in a single document, the transfer of ownership is executed only after the lease period ends. This practice complies with KHES Articles 322–329 and the DSN-MUI Fatwa, and functions as an alternative sharia-compliant financing model for micro-based cooperative businesses.